Does ability-based emotional intelligence contribute to school achievement of elementary school pupils? - Babić Čikeš, Ana (Array, 2012)
The study was designed to test the hypothesis about the contribution of different facets of ability-based emotional intelligence in explaining school achievement in elementary school children controlling for basic demographic features and certain aspects of personality. One hundred and thirty three pupils of 5th, 6th, 7th, and 8th primary school graders of both gender in Croatia completed three emotional intelligence tests, Empathy self-report questionnaire and Rosenberg self-esteem scale, and reported on their mathematics and foreign language grades as well. Emotional intelligence tests showed significant contribution to school achievement and explained 16.2% of additional criterion variance. The obtained results can be regarded as an evidence of criterion validity for the used EI measures and also as encouragement for further investigation of emotional intelligence in this age group.